Expertise in striking sports: The importance of visual anticipation for superior performance. - Morris-Binelli, K. (Murdoch University, 2016)
Superior performance in striking sports such as baseball requires anticipatory skill due to constraints imposed on performers, which make it extremely difficult to achieve motor skills such as hitting a baseball. This paper provides an updated literature review of visual anticipation in striking sports and addresses whether there have been advancements in striking sport research which add to a model of visual anticipation proposed by Müller and Abernethy (2012). Firstly, this paper provides an overview of visual anticipation theory and methodologies used to study visual anticipation, followed by a review of recent empirical findings. Specifically, this review addresses advancements in the literature in relation to multiple factors influencing visual anticipation performance between varying skill levels. Furthermore, whether anticipatory skill can be learnt and whether anticipatory skill can transfer to similar or dissimilar domains is discussed. Subsequently, this review highlights that multiple factors contribute to anticipatory skill, as well as identifying viable methods to improve visual anticipation. Moreover, evidence that anticipatory skill can transfer to similar domains is discussed, but it is apparent further research is required, due to scarce research in this area. Collectively, this review provides an update of the research on visual anticipation in striking sports and highlights findings that further the understanding of expertise in striking sports.